k = 1 ∑ ∞ k 2 ( 4 3 ) k
Find the value of the sum above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S = k = 1 ∑ ∞ k 2 ( 4 3 ) k = k = 0 ∑ ∞ ( k + 1 ) 2 ( 4 3 ) k + 1 = 4 3 k = 0 ∑ ∞ k 2 ( 4 3 ) k + 2 3 k = 0 ∑ ∞ k ( 4 3 ) k + 4 3 k = 0 ∑ ∞ k ( 4 3 ) k = 4 3 S + 2 3 k = 0 ∑ ∞ k ( 4 3 ) k + 4 3 ( 1 − 4 3 1 ) Note that S = k = 1 ∑ ∞ k 2 ( 4 3 ) k = k = 0 ∑ ∞ k 2 ( 4 3 ) k
⟹ 4 S ⟹ S = 2 3 k = 0 ∑ ∞ k ( 4 3 ) k + 3 = 2 3 ( 1 2 ) + 3 = 8 4 Using the same method (see note).
Note:
S 1 ⟹ 4 S 1 ⟹ S 1 = k = 0 ∑ ∞ k ( 4 3 ) k = k = 1 ∑ ∞ k ( 4 3 ) k = k = 0 ∑ ∞ ( k + 1 ) ( 4 3 ) k + 1 = 4 3 k = 0 ∑ ∞ k ( 4 3 ) k + 4 3 k = 0 ∑ ∞ ( 4 3 ) k = 4 3 S 1 + 3 = 3 = 1 2
Problem Loading...
Note Loading...
Set Loading...
First note that for l x l < 1 we have
∑ k = 1 ∞ ( x k ) = x / ( 1 − x ) .
Now differentiate both sides and multiply through by x to find that
∑ k = 1 ∞ ( k ∗ x k ) = x / ( 1 − x ) 2 .
Differentiate both sides again and multiply through by x to find that
∑ k = 1 ∞ ( k 2 ∗ x k ) = x ∗ ( 1 + x ) / ( 1 − x ) 3 .
Now just plug in x = 3 / 4 to find that the sum comes to 8 4 .
I realize that this is more of a calculus approach as opposed to algebraic, but it was the most efficient method I could think of applying to the problem.